SCREENING OF POTENTIAL CORE GENES IN PERIPHERAL BLOOD OF ADULT PATIENTS WITH SEPSIS BASED ON TRANSCRIPTION REGULATION FUNCTION. Issue 3 (27th March 2023) - Liu, Jitao; Li, Shaolan; Xiong, Dianhui; Shang, Wenjun; Zhan, Tao; Zhu, Xingxin; He, Sheng; Wang, Yu; Zhang, Qian; Hu, Yingchun
ABSTRACT: Objective: The aim of the study is to screen transcription factor genes related to the prognosis of adult patients with sepsis. Methods: Twenty-three patients with sepsis and 10 healthy individuals admitted for RNA-seq. Differential factors were enriched by four transcription factor databases, and survival analysis was adopted for core factors. Then, target genes were submitted to STRING to constitute the protein-protein interaction network. Single-cell technology was used to localize cell lines. Finally, a transcription-target gene regulation network was constituted. Results: A total of 4, 224 differentially expressed genes were obtained between sepsis and normal control groups. Protein-protein interaction results showed that FOXO3, NFKB1, SPI1, STAT5A, and PPARA were located in the center of the network. Target genes were related to cytokine-mediated signaling pathway and transcription regulator activity, etc. SPI1 was mainly located in monocyte cell lines, while FOXO3, PPARA, SP1, STAT3, and USF1 were expressed in monocyte cell lines, NK-T cell lines, and B cell lines. Compared with those in the control group, FOXO3, SP1, SPI1, STAT3, and USF1 were highly expressed in the sepsis group, while PPARA had low expression. Conclusions: Transcription factors, such as FOXO3, PPARA, SP1, SPI1, STAT3, and USF1, are correlated with the prognosis of sepsis patients and thus may have a potential research value. Clinical Trial Registration: The clinical trial registration number is ChiCTR1900021261.